An analysis of awareness, understanding, and usage of disruptive technologies in the construction economy - Bujang Hassim, Nur Syamilah; Razali, Mohd Norhisham; Lee, Wen Chiat; Bennied, Neilhubila; Hanapie, Rozita; Weif, Yong Sze (Universiti Teknologi MARA Selangor, 2026)
The adoption of disruptive technologies is increasingly recognized as essential to transforming the construction economy. However, the adoption in Malaysia remains limited compared to other sectors despite government initiatives such as the Construction 4.0 Strategic Plan. This study aims to examine the levels of awareness, understanding, and usage of disruptive technology among construction players in Sarawak. A quantitative research design is used. The data were collected from 132 respondents across 91 companies, representing a diverse group of mid- career professionals, mostly employed in specialized trades and higher- grade firms. The findings indicate that respondents are more aware of technologies such as cloud computing, real-time collaboration, and artificial intelligence (AI). However, awareness of blockchain and autonomous construction remains relatively low. Although usage remains relatively low, the adoption is increasing, with 35.6% of respondents using technology compared to 10% in earlier studies. These results highlight a gap between awareness and actual adoption, suggesting the need for targeted training and awareness programs to align with the industry practices with the Construction 4.0 Strategic Plan goals.